The Effect of a Cyclic Inquiry Model in Mathematical Proficiency of Second Class Female Students Noor Abdulwahid Al-Rubaiy - Abdulkadiam Al-Taie, Taghreed (Opción, 2019)
The objective of the research was to identify the effect of the periodic survey model on the mathematical proficiency of second grade students. The expe- riment was applied to a sample of 69 students, the experimental group 34 students and the control group (35) For the academic year 2018 (2019), the two groups were rewarded in variables (age of female students calculated by months, IQ test, previous achievement in mathematics, previous math test, mathematical skill test with previous information). The mathematical profi- ciency test consisted of (23) objective and transitional subjects. The measure of the inclination produced towards mathematics consisted of (30) paragra- phs. The validity of the test and the scale were verified. The coefficient of their stability was acceptable , And the coefficient of difficulty and discrimi- nation and the effectiveness of the wrong substitutes for the test paragraphs were good. The coefficient of discrimination for the scales of the inclination produced for mathematics was also good. After the experiment, both the mathematical proficiency test and the inclination measure for mathematics were applied to both groups ). The t-test was used to treat the data. The results of the study showed that there was a statistically significant differen- ce at the level of (0.05) between the average scores of the experimental group and the students of the control group in the mathematical skill as a whole, .